THE POSITION OF THE GUARANTOR IN RECONCILIATION ON THE BANKRUPTCY ACT ACCORDING TO THE LAW OF BANKRUPTCY IN INDONESIA - Siti Mahmudah; Siti Malikhatun Badriyah; Bagus Rahmanda (Diponegoro Law Review, 2018)
The existence of the guarantor in the world of business is widely known and required in the business world. Guarantor is stipulated in the agreement of guarantor which states that the Guarantor will pay the debt of debtor to its creditor if the debtor do not pay. The debt fulfillment of debtor to creditor  can be done through the Bankruptcy Act which ended with reconciliation. The purpose of this research is to examine the position of the Guarantor in reconciliation on the Bankruptcy Act according to the Law of Bankruptcy in Indonesia, with the problem of how the position of the guarantor against debt fulfillment of debtor which ended with reconciliation in bankruptcy in Indonesia, and as a result of the approval of reconciliation in the bankruptcy of the submission of the claim the statement of bankrupt guarantor. The approach used in this research is the normative juridical, with a descriptive specifications analysis with the type of secondary data through the study of primary, secondary and tertiary legal material library which is then analyzed by qualitative research. The reconciliation that passed in bankruptcy does not always result to receivables of the creditors being paid for. Based on the provisions of Article 165 paragraph (1) Of Law No. 37 Of 2004 on Bankruptcy and Suspension of Obligation for Payment of Debts,Guarantor will still be obligated to pay off the debtor's debts that are borne which can cause the guarantor privileged as the debtor so it can be filed for bankruptcy if fulfilled the provisions of Article 2 paragraph (1) Of Law No. 37 Of 2004 on Bankruptcy and Suspension of Obligation for Payment of Debts.